2008
DOI: 10.1007/s10815-008-9250-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of magnetic activated cell sorting of non-apoptotic spermatozoa before density gradient centrifugation for assisted reproduction

Abstract: Purpose Magnetic activated cell sorting (MACS) eliminates apoptotic spermatozoa based on the presence of externalized phosphatidylserine residues. We evaluated the outcome of male fertility treatment when intracytoplasmic sperm injection (ICSI) into human oocytes was performed with non-apoptotic MACS-selected spermatozoa. Methods 196 couples were treated by ICSI following spermatozoa preparation by MACS (study group; 122 couples) or density gradient centrifugation (DGC) (control group; 74 couples). Fertilizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
1
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(118 citation statements)
references
References 33 publications
5
91
1
5
Order By: Relevance
“…Citation: García-Ferreyra J, Villegas L, Romero R, Zavala P, Hilario R, et al (2014) High Pregnancy and Implantation Rates Can Be Obtained Using Magnetic-Activated Cell Sorting (MACS) to Selection Spermatozoa in Patients with High Levels of Spermatic DNA Fragmentation. JFIV Reprod Med Genet 3: 133. doi:10.4172/2375-4508.1000133 Several studies reported an improvement in fertilization rates [15,16] and embryo quality [17][18][19] because the best sperms were selected using MACS compared to standard selection methods. On the other hand, Gil et al [20] showed that the implantation and miscarriage rated did not vary between MACS or standard sperm selection methods; however, they did observe an improvement in pregnancy rates.…”
Section: Discussionmentioning
confidence: 99%
“…Citation: García-Ferreyra J, Villegas L, Romero R, Zavala P, Hilario R, et al (2014) High Pregnancy and Implantation Rates Can Be Obtained Using Magnetic-Activated Cell Sorting (MACS) to Selection Spermatozoa in Patients with High Levels of Spermatic DNA Fragmentation. JFIV Reprod Med Genet 3: 133. doi:10.4172/2375-4508.1000133 Several studies reported an improvement in fertilization rates [15,16] and embryo quality [17][18][19] because the best sperms were selected using MACS compared to standard selection methods. On the other hand, Gil et al [20] showed that the implantation and miscarriage rated did not vary between MACS or standard sperm selection methods; however, they did observe an improvement in pregnancy rates.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sperm sample parameters that are improved in the subpopulation selected by MACS include: sperm motility and morphology, sperm DNA damage and hamster oocyte penetration potential of spermatozoa (Lee et al, 2010;Said et al, 2006a;Said et al, 2006b). Clinical pregnancy data collected so far indicate that the use of MACS may be of especial value for cases of male infertility associated with high incidence of apoptotic and DNA damaged sperm (Dirican et al, 2008).…”
Section: Magnetic-activated Cell Sorting (Macs)mentioning
confidence: 99%
“…As a result, a wide variety of techniques have been tried based on current knowledge in the hope of improving pregnancy outcomes. These include externalisation of phosphotidylserine (magnetic-activated cell sorting), 32 cell charge (zeta charge), 33 maturity markers (hyaluronic acid binding) [34][35][36] and detailed morphological analysis (intracytoplasmic morphologically selection sperm injection). [37][38][39][40] .…”
Section: Sperm Function Testing and Icsimentioning
confidence: 99%